First results of the experiment to search for 2β decay of 106Cd with the help of 106CdWO4 crystal scintillators - P. Bell; R. Bernabei; R. S. Boiko; V. B. Brudanin; F. Cappella; V. Caracciolo; R. Cerulli; D. M. Chernyak; F. A. Danevich; S. d'Angelo; A. E. Dossovitskiy; E. N. Galashov; et al. (Ядерна фізика та енергетика)
An experiment to search for 2β processes in 106Cd with the help of 106CdWO4 crystal scintillator (mass of 215 g), enriched in 106Cd up to 66 %, is in progress at the Gran Sasso National Laboratories of the INFN (Italy). After 1320 h of data taking, limits on double beta processes in 106Cd have been established on the level of 1019 − 1020 yr, in particular (all the results at 90 % C.L.): T1/2(0ν2ε) > 3.6 · 1020 yr, T1/2(2νεβ+) > 7.2 · 1019 yr, and T1/2(2ν2β+) > 2.5 · 1020 yr. Resonant 0ν2ε processes have been restricted as T1/2(0ν2K) > 1.4 · 1020 yr and T1/2(0νLK) > 3.2 · 1020 yr. A possible resonant enhancement of the 0ν2ε processes is estimated in the framework of the QRPA approach.